Pendidikan Karakter Berbasis Pancasila : Peran Sila Pertama dalam Pembentukan Karakter Siswa di Sekolah - Abel Apri Nabila; M. Farhan Yusuf; Muhammad Rafi; Wahyu Fatur Rahmawan; Herli Antoni (Institut Nalanda, 2024)
Character education in elementary schools is an important foundation in building a young generation that is religious, ethical, and virtuous. The first precept of Pancasila, namely the One Godhead, is the main foundation in instilling moral values, faith, and piety from an early age. The research aims to examine the meaning and role of the first precept of Pancasila in building character education for elementary school students. Using the literature study method, this study analyzes a variety of literature, including books, scientific journals, and relevant official documents. The analysis was carried out descriptively to understand the contribution of the value of the One God in shaping the character of students. The results of the study show that the application of divine values through integration in the curriculum, religious activities, and strengthening a tolerant environment in elementary schools can increase religiosity, ethics, and mutual respect for students. In conclusion, the first precept of Pancasila provides a solid foundation for character formation in elementary schools. For this reason, further support is needed through teacher training and the provision of inclusive educational resources.